Introduction to Numbers in Mobile-Based For Early Childhood - Vika Febri Muliati; Fesa Asy Syifa Nurul Haq; Muhammad Zarlis; Ucuk Darusalam; Abdu Rahman (Jurnal Informatika, 2026)
Child age early in the current era This faced on Lots existing technology environment around , among them is cellphone , television , And computer . Application multimedia capable interesting attention And interest student in the learning process Because served in form picture as well as animation , proven by 80% from 26 respondent agreed matter the . Wrong One ability Which currently develop moment age early is ability speak . Child age early demanded For can quick learn And understand numbers . But problem Which happen moment this , Still Lots child age early Which Still difficult in do learning For know numbers . No only it , still Lots also parents who still difficulty in do teaching because that child not enough interested with the learning process . By Because it , build it system application introduction letter And number For child age Early with utilise Visual. Keyword — Child  Early Age , Introduction numbers , Visual.